Laryngeal Mask Ventilation during Neonatal Resuscitation: A Case Series - Lauren White; Katelyn Gerth; Vicki Threadgill; Susan Bedwell; Edgardo G. Szyld; Birju A. Shah (MDPI AG, 2022)
Positive pressure ventilation via a facemask is a critical step in neonatal resuscitation but may be a difficult skill for frontline providers or trainees to master. A laryngeal mask is an alternative to endotracheal intubation for some newborns who require an advanced airway. We present the first case series in the United States in which a laryngeal mask was successfully utilized during resuscitation of newborns greater than or equal to 34 weeks' gestation following an interdisciplinary quality improvement collaborative and focused training program.